HIV PREVALENCE AMONG ANTENATAL MOTHERS IN TERENGGANU - Balkis AK; Zahari CD (Malaysian Journal of Public Health Medicine, 2003)
National Antenatal HIV Screening Programme has been integrated as a routine screening in antenatal care in early 1998 and in Terengganu since May 1998 involving all health centers in the state. As of December 2001, a total number of 57,882 antenatal mothers were screened (97.5% of all new antenatal mothers). The HIV prevalence rate among antenatal mothers was found to be 0.052%. All HIV positive mothers were married and majority were Malays (93.3%). Ninety percents of them revealed that the only risk factor for HIV was through sexual contact. HIV positive status was confirrned in 66 .7% of the husbands. All twenty eight mothers that managed to be followed up delivered to live birth babies. All newborns reported to have good Apgar score (9 at 5 minutes of life). Mean birth weight was 3 .08 kilograms Â± 0.45 and only 8% were premature babies. The observed rate of HIV vertical transmission was 6.25% and this is lower than the expected mother to child transmission rate of 30% without intervention.